Genomic Organization and Promoter Characterization of RANTES, MIP-1ß like and MCP-Like CC Chemokines of Domestic Duck (Anas platyrhynchos) - Arathy, D.S.; Sreekumar, E. (International Journal of Poultry Science, 2009)
The duck immunology is gaining more interest in recent years since ducks have been identified as “Trojan horse ” of highly pathogenic avian influenza. In the present study, we characterize the gene and promoter regions of three CC chemokines from domestic duck. Analysis of the gene revealed significant similarity with chicken and mammalian chemokine genes with three coding exon and two intron pattern. Though the exons are highly conserved with respect to corresponding chicken chemokine genes, introns revealed low identity. Promoter regions of duck RANTES and MCP-like chemokines were amplified by Genome walking method. Analysis of the 500 bp upstream nucleotide sequences of ATG (translational start site) of RANTES and MCP-like chemokine revealed a number of putative binding sites for transcription factors. Comparative analysis of RANTES promoter with human and chicken sequences revealed conserved TATA box, NFkB binding site and transcription start site. The predicted transcription start site and TATA box are also conserved in duck and chicken MCP-like chemokine sequences. The present study shows that the over all organization of gene and putative transcription factor binding sites in the promoter regions of these three chemokines were conserved with respect to chicken and human sequences indicating these molecules of innate immune system is conserved in the process of evolution.